Analisis Pemanfaatan Panel Surya Tipe Polycrystalline 100 Wp Sebagai Sumber Energi Alternatif Untuk Meningkatkan Kesejahteraan Masyarakat Pedesaan Di Indonesia - Fakhira, Arini Azrin; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Solar energy is an alternative energy source that is environmentally friendly and has great potential to be utilized in Indonesia. However, the use of solar energy is still limited, especially in rural areas which have limited infrastructure and access to electricity. This research aims to analyze the use of 100 WP polycrystalline solar panels as an alternative energy source to improve the welfare of rural communities in Indonesia. The research method used is literature review, namely by examining and criticizing various reference sources that are relevant to the research topic. The data collected includes secondary data, which was analyzed using content analysis, comparative analysis and synthesis analysis techniques. The research results show that the use of 100 WP polycrystalline solar panels can provide benefits for rural communities, including: (1) increasing the availability and quality of electricity, (2) saving costs on fossil fuels (3) reducing greenhouse gas emissions, (4) improve the quality of life and public health. This research recommends that the use of 100 wp polycrystalline solar panels can be expanded and improved in other rural areas in Indonesia, taking into account technical, economic, social and environmental aspects.